NOT CARELESS BUT WEAK: LANGUAGE MIXING OF MALAYSIAN CHINESE IN A BUSINESS TRANSACTION - Kuang Ching Hei; Maya Khemlani David (University of Kuningan, 2015)
Language is an inevitable tool for business transactions and regardless of nationality, ethnicity, gender, religion, age and social class, interlocutors depend on it to conduct their daily dealings. In multilingual and multicultural Malaysia, it is not uncommon to hear a business transaction being conducted in various languages depending on who the participants are and what the context involves. This study focussed on the phenomenon of language (code) mixing within a business transaction that involved four Malaysians of Chinese descent. The study aimed to detect at what level language mixing occurred and what their functions would be. Data were video recorded and then transcribed verbatim. Mandarin utterances were documented in Chinese and Han Yu Pin Yin and provided with translations. Utterances containing a mixture of languages were then extracted for analysis. Findings suggest that language mixing occurred at the word, phrase, sentential and tag level. Language mixing was applied as a strategy to sustain the conversation mainly because of the interlocutors’ weak proficiency in specific languages. It was also employed for various functions such as for distancing or narrowing the social status, making emphasis and projecting a higher personal identity. A follow up interview is required in order to verify the extent of the participants’ low or high proficiency level in the various languages used in this context. Keywords: language mixing, Malaysian, business transaction, communication